2017
DOI: 10.1108/qram-05-2016-0044
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise systems, business process management and UK-management accounting practices

Abstract: Purpose This paper aims to address the extant and arguable role of enterprise systems (ES) in relation to management accounting practices (MAPs) through an inclusion relative neglect account of business process management (BPM). This is also extended to draw out an analytical framework to advance our understanding of how BPM mediate ES-MAPs interplay. Design/methodology/approach A cross-sectional case study was adopted as a research strategy with which to collect data about the ES-BPM-MAPs interplay as a uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
1
10
0
1
Order By: Relevance
“…For instance, ERP adoptions by Greek companies were driven by their needs in an increasingly competitive environment in order that they could survive and/or succeed (Spathis and Constantinides, 2004). In the UK context, Ammar (2017), it was noticed that variations in management accounting practices that are due to ERP mobilisation have been used to address different managerial functions, including planning and decision‐making, across multiple cases operating in the UK context. Similarly, Goumas et al (2018) reported that ERP demonstrated various implications, both within and across different manufacturing categories, both for reducing uncertainty and for improving operations and managerial decision‐making.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…For instance, ERP adoptions by Greek companies were driven by their needs in an increasingly competitive environment in order that they could survive and/or succeed (Spathis and Constantinides, 2004). In the UK context, Ammar (2017), it was noticed that variations in management accounting practices that are due to ERP mobilisation have been used to address different managerial functions, including planning and decision‐making, across multiple cases operating in the UK context. Similarly, Goumas et al (2018) reported that ERP demonstrated various implications, both within and across different manufacturing categories, both for reducing uncertainty and for improving operations and managerial decision‐making.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…According to Ammar (2017) AIS are constituted by features including: people, procedure and instructions, data, technology (hardware and software), information technology infrastructure, and internal controls. People are system users of accounting systems, includingsystem administrators, designers, managers, accountants, business analysts, auditors, chief financial officers, and other professionals.…”
Section: Relevant Scholarshipmentioning
confidence: 99%
“…Hal inilah yang kemudian mendasari hadirnya beragam metode penentuan harga jual di era modern saat ini. Untuk menetapkan harga jual yang tepat, berbagai faktor dijadikan titik penentu, di antaranya dengan mengacu pada penetapan harga pokok produk dan mark up yang tepat (Ammar, 2017;Stanley, 2017;Warwick & Robert, 2014).…”
Section: Hasil Dan Pembahasanunclassified